PELAKSANAAN PROGRAM PEMBANGUNAN EKONOMI MASYARAKAT DI BAITUL QIRADH BINA INSAN MANDIRI (BQ-BIMA) BANDA ACEH Patmawati - Patmawati Haji Ibrahim; Junaidi Junaidi (Sharia and Law Faculty, 2017)
The study of the establishment of economic building program of Baitul Qiradh Bina Insan Mandiri (BQ-BIMA) Banda Aceh aimed at analysing the type of the establishment of community economic building program in Banda Aceh and intended to examine Syariah principle implemented by BQ- BIMA when financing for business capital to clients. In achieving this goals, the researcher used interview and observation as the primary source in collecting data while books, journals, magazines and other sources related to the issue of this study are regarded as secondary references. In addition, inductive and deductive analysis of qualitative method were used in analysing the data. Inductive analysis in the form of interview initiated the type of economic building program established by BQ-BIMA Banda Aceh. Indeed, deductive method from observation, books, journals and other related sources added more information in summaryzing the type of establishment of this program. Through investigation and analysis it was found that the program run by BQ-BIMA Banda Aceh was funding project for home industry and peniaga kecil aman dari terjadinya keredit macet. BQ-BIMA Banda Aceh applies the following procedure in giving the loan: understanding the characteristic of consumer need, undertanding (human capacity), (capital), (economic condition), (collateral), and the right implementation of Fiqh principles. Furthermore, BQ-BIMA also supervised the client that they are able to return the loan in time, the bond was physically conquered, administration of debitor company was made neat and organized as well as supervised. The establisment of community economic building program of BQ-BIMA support the implementation of Islamic economy principles, assisting other, business, avoiding